2021
DOI: 10.1093/ckj/sfab275
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory blood pressure trajectories and blood pressure variability in kidney transplant recipients: a comparative study against haemodialysis patients

Abstract: Background Hypertension is the most prevalent cardiovascular risk factor in kidney-transplant-recipients (KTRs). Preliminary data suggest similar ambulatory-blood-pressure (ΒP) levels in KTRs and hemodialysis (HD) patients. This is the first study evaluating in comparison the full ambulatory-BP-profile and short-term BP-variability (BPV) in KTRs versus HD patients. Methods Two-hundred-four KTRs were matched (2:1 ratio) with 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…This is the first study to compare short-term BPV between KTRs and CKD patients without kidney replacement therapy, showing no significant differences between the two study groups in all indices studied except for DBP SD. Based on these observations and previous findings that KTRs have significantly lower BPV compared with hemodialysis individuals [ 25 ], one could hypothesize that BPV levels are improved after kidney transplantation to a level comparable to that of CKD patients without kidney replacement therapy with similar eGFR. Possible explanations for this improvement include BP lowering and downregulation of sympathetic nervous system overdrive observed after kidney transplantation [ 31 ].…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…This is the first study to compare short-term BPV between KTRs and CKD patients without kidney replacement therapy, showing no significant differences between the two study groups in all indices studied except for DBP SD. Based on these observations and previous findings that KTRs have significantly lower BPV compared with hemodialysis individuals [ 25 ], one could hypothesize that BPV levels are improved after kidney transplantation to a level comparable to that of CKD patients without kidney replacement therapy with similar eGFR. Possible explanations for this improvement include BP lowering and downregulation of sympathetic nervous system overdrive observed after kidney transplantation [ 31 ].…”
Section: Discussionmentioning
confidence: 60%
“…To the best of our knowledge, studies comparing mean ambulatory BP values between KTRs and CKD patients (including both CKD patients without kidney replacement therapy and individuals undergoing hemodialysis) are scarce. Α few studies comparing KTRs and hemodialysis patients with ABPM showed that both groups generally display similar BP levels [ 23 , 24 ]; however, in a recent study by our group, which is currently the largest in the field, SBP and PP levels were significantly lower in KTRs compared to hemodialysis patients, and BP trajectories differed accordingly [ 25 ]. With regards to CKD patients without kidney replacement therapy, in the only study to date comparing the mean ambulatory BP values between 92 KTRs and 97 CKD patients, 24-hour SBP, as well as awake and sleep SBP were significantly higher in KTRs, while office BP was not [ 14 ].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The dipping pattern of nocturnal BP was calculated with the following formula: 1 − mean night/mean day ratio of systolic BP (SBP) (%). Patients were categorized into four groups: extreme dippers (nocturnal BP decrease of >20%), dippers (decrease of >10% but ≤20%), non-dippers (decrease of ≥0% but ≤10%) and reverse dippers (nocturnal increase in SBP) [ 19 ]. The pre-awakening morning SBP surge was calculated as the difference between the average of the 2 h after awaking minus the average of the 2 h pre-awakening, as previously described [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…Current literature suggests that KTx is associated with improved BP levels in transplant recipients compared with the pre-transplant condition [ 17 , 18 ] or patients on dialysis [ 19 ]. In addition, BP levels in kidney donors do not appear to change significantly after renal transplantation [ 20–23 ].…”
Section: Introductionmentioning
confidence: 99%